2010
DOI: 10.1039/c0cc00217h
|View full text |Cite
|
Sign up to set email alerts
|

Backscattered electron (BSE) imaging of platinum nano-particles dispersed in mesoporous silica

Abstract: High-resolution scanning electron microscopy (HR-SEM) with backscattered electrons (BSE) under a low accelerating voltage provided images with compositional information about Pt nano-particles with a diameter of approximately 6 nm that were dispersed in mesoporous silica (SBA-15). The dispersion of Pt nano-particles in mesoporous silica was investigated using the BSE imaging method in combination with the broad ion beam (BIB) cross-section fabrication technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The SiO 2 structures uncoated with metal were observed using an S-4800 field emission-SEM at an acceleration voltage of 0.8–2 kV (Hitachi High-Technologies, Japan). For the cross-sectional SEM image, the specimens were milled with a broad ion beam (E-3500, Hitachi High-Technologies) …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiO 2 structures uncoated with metal were observed using an S-4800 field emission-SEM at an acceleration voltage of 0.8–2 kV (Hitachi High-Technologies, Japan). For the cross-sectional SEM image, the specimens were milled with a broad ion beam (E-3500, Hitachi High-Technologies) …”
Section: Experimental Sectionmentioning
confidence: 99%
“…For the cross-sectional SEM image, the specimens were milled with a broad ion beam (E-3500, Hitachi High-Technologies). 30 ■ RESULTS AND DISCUSSION Formation of Siloxane/PS−P4VP Complexes. FT-IR spectra of PS−P4VP and the PS−P4VP/siloxane complexes were obtained to investigate the interaction between PS−P4VP and siloxane.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The SEM of the biomaterials after drug loading did not show any changes in the biomaterials microstructure and revealed micrometric precipitates of carboplatin, as well as mannitol on the CaPs surface. Backscattered electron analysis was used to highlight the platinum element in different matrices [72][73][74][75]. This technique uses the signal of the elastic interaction between the electron beam and the specimen.…”
Section: Plos Onementioning
confidence: 99%
“…The previous research studies have demonstrated that the evaluation of the dispersity of inorganic particles should consider both the secondary sizes of the aggregated particles and the uniformity of the particle distribution. 20,21 To acquire this information, scanning electron microscopy (SEM), 22,23 transmission electron microscopy (TEM) 24,25 and theoretical modeling [26][27][28] have been carried out previously. Disappointingly, SEM and TEM can usually provide two-dimensional observation results from a single plane in the composite materials.…”
mentioning
confidence: 99%